Audiovisual Integration Delayed by Stimulus Onset Asynchrony Between Auditory and Visual Stimuli in Older Adults. (February 2017) - Ren, Yanna; Yang, Weiping; Nakahashi, Kohei; Takahashi, Satoshi; Wu, Jinglong
Although neuronal studies have shown that audiovisual integration is regulated by temporal factors, there is still little knowledge about the impact of temporal factors on audiovisual integration in older adults. To clarify how stimulus onset asynchrony (SOA) between auditory and visual stimuli modulates age-related audiovisual integration, 20 younger adults (21–24 years) and 20 older adults (61–80 years) were instructed to perform an auditory or visual stimuli discrimination experiment. The results showed that in younger adults, audiovisual integration was altered from an enhancement (AV, A ± 50 V) to a depression (A ± 150 V). In older adults, the alterative pattern was similar to that for younger adults with the expansion of SOA; however, older adults showed significantly delayed onset for the time-window-of-integration and peak latency in all conditions, which further demonstrated that audiovisual integration was delayed more severely with the expansion of SOA, especially in the peak latency for V-preceded-A conditions in older adults. Our study suggested that audiovisual facilitative integration occurs only within a certain SOA range (e.g., −50 to 50 ms) in both younger and older adults. Moreover, our results confirm that the response for older adults was slowed and provided empirical evidence that integration ability is much more sensitive to the temporal alignment of audiovisual stimuli in older adults.